Biceps Tenosynovitis in the Dog: Radiographic and Sonographic Findings - Rivers, B.; Wallace, L.; Johnston, G. R. (Veterinary and Comparative Orthopaedics and Traumatology, 1992)
Ultrasonography of the biceps brachii tendon was prospectively evaluated as an ancillary diagnostic technique in comparison to arthrography in canine biceps tenosynovitis, in a series of six cases with surgical and histopathological confirmation of the diagnosis. Arthrographic findings, compatible with the disease, were present in all six cases, and correlated well with surgical findings. Significant differences were not found in the sonographic appearance of the affected versus the contralateral unaffected biceps brachii tendon proper. In two cases, sonography demonstrated a sonolucency surrounding the affected tendon; in one of these cases effusion within the biceps tendon sheath was noted at operation. In a third case, sonographic findings correlated with the presence of periosteal proliferation within the intertubercular groove noted on survey radio-graphs. Based on these six cases, arthrography appears to be a more sensitive ancillary diagnostic technique in this disorder than ultrasonography of the biceps brachii tendon.Ultrasonography was prospectively evaluated in comparison to arthrography as an ancillary diagnostic technique in six cases of canine biceps tenosynovitis with surgical and histopathological confirmation of the diagnosis. Results obtained indicate arthrography appears to be a more sensitive ancillary diagnostic technique than ultra-sonography in this disorder.
Keywords: Biceps; tenosynovitis; arthrography; ultrasonography